One-pot preparation of CuOx-CoOy heterostructure decorated on graphene for highly efficient oxidation of 5-hydroxymethylfurfural (5-HMF) to 2, 5-furandicarboxylic acid (FDCA). (23rd November 2022) - Rao, Minhui; Wang, Mengyu; Zheng, Xuelin; Pan, Danmei; Hong, Congbin; Chen, Kaidong; Lin, Liangxu
Graphical abstract: Dense CuOx -CoOy nano-heterostructures were uniformly assembled on the surface of graphene by one-pot method under mild reaction conditions through the induced assembly of PVP and reduction of NaBH4 . Owing to the combination (e.g. suitable surface electronic structure and good catalytic kinetics) of graphene and CuOx -CoOy heterostructures, this material exhibited excellent selectivity, catalytic activity and cycle stability in the oxidation of HMF to value-added chemical FDCA with NaClO as oxidant at 30 °C. Highlights: Dense CuOx -CoOy heterostructures assembled on graphene surface by one-pot method. PVP reduced the size of CuOx -CoOy and enhanced metal loading on graphene. Heterostructure regulated electronic states and promoted charge transfer process. CuOx -CoOy -PVP/G shows high catalytic performance on the conversion of HMF to FDCA. Abstract: Dense CuOx -CoOy nano-heterostructures were uniformly assembled on the surface of graphene via surfactant induced assembly and hydrolysis with the presence of PVP and NaBH4 . As-prepared CuOx -CoOy -PVP/G composite exhibited excellent performance for selective oxidation of 5-HMF to FDCA in aqueous solution with NaClO as oxidant at 30 °C, which is comparable to noble metal catalysts. The outstanding performance can be attributed to fascinating synergetic contributions from the CuOx -CoOy heterostructure on graphene substrate, giving improved interfacial contact, increased active sites and accelerated electron transfer process to promote the catalytic reaction. This work provides a high-performing catalyst for oxidation of 5-HMF to FDCA, as well as an ideal design of metal-oxide heterostructures/graphene composite catalysts for more broad applications.